Histopathologic Characterization of Bladder Perivascular Epithelioid Cell Neoplasms (PEComa): A Series of 11 Cases With a Subset Having TFE3 Rearrangements. (February 2021) - Neumann, Neil M.; Haffner, Michael C.; Argani, Pedram; Kao, Chia-Sui; Epstein, Jonathan I.
Abstract : Perivascular epithelioid cell neoplasms (PEComas) of the bladder are extremely rare, with 30 case reports. A subset of PEComas contain TFE3 gene rearrangement, however, the distinct histomorphologic features of these translocation tumors has not been fully explored in bladder PEComas. In our series, 11 cases of bladder PEComas were collected, including 1 internal and 10 consults, with 1 case previously reported. There was a female predominance (9 female, 2 male) with a mean age of 44.2 years (24 to 61 y). In only 1 of the 10 consult cases was PEComa considered in the differential diagnosis. In 10 of 11 cases, prominent epithelioid features were noted, with the final case having focal epithelioid morphology. Mitotic rate was increased in 2 of 11 cases, and 2 of 11 cases had cytological atypia. Two cases were malignant, with invasion into perivesicle tissue in 1 case, and metastases to lungs and brain followed by death in the other case. Immunohistochemically, there was strong, and diffuse staining for cathepsin K in 10/11 cases with the 1 negative case restained on a previously stained slide. HMB-45 was diffusely positive in 8/11 cases, while melan-A was present in only 1/10 cases. Muscle markers were variably expressed with positivity for both smooth muscle actin in 6/10 cases and desmin in 3/10 cases. Keratin AE1/3 was uniformly negative (0/11). In 5/8 cases where TFE3 was rearranged by fluorescence in situ hybridization, the morphology had a predominantly epithelioid, nested architecture. Overall, bladder PEComas are particularly difficult to diagnose given their rarity, are predominantly epithelioid and do not always express melanocytic markers. Diagnosis in the bladder requires a combination of morphologic characterization, exclusion of other diagnostic possibilities, positive Cathepsin K staining, variable melanocytic marker expression, with some cases showing a TFE3 gene rearrangement.